Analysis of the Productivity of Hybrid Corn Variety Bisi 2 in Buleleng Village, Bungku Pesisir Subdistrict, Morowali Regency, Central Sulawesi Province - Jusmital; Surni; Fyka, Samsul Alam (International journal of technology and education research, 2025)
The purpose of this study was to determine: how much is the productivity of hybrid corn variety bisi 2 in Buleleng Village, Bungku Pesisir District, Morowali Regency, Central Sulawesi Province and what factors influence the productivity of hybrid corn variety bisi 2 in Buleleng Village, Bungku Pesisir District, Morowali Regency, Central Sulawesi Province. The population in this study were all corn farmers in Buleleng Village, totaling 36 people. This study used a census method, where the entire population was used as a sample. Data were analyzed using a multiple non-linear regression formula transformed into a Cobb Douglas function. The results of this study indicate that the factors that affect the productivity of hybrid corn bisi 2 are farming experience X1 with a significant value of 0.041, the use of technology X2 with a significant value of 0.015, and the use of seeds X3 with a significant value of 0.002.